Association of Emerging β-Amyloid and Tau Pathology With Early Cognitive Changes in Clinically Normal Older Adults. (12th April 2022) - Farrell, Michelle E.; Papp, Kathryn V.; Buckley, Rachel F.; Jacobs, Heidi I.L.; Schultz, Aaron P.; Properzi, Michael J.; Vannini, Patrizia; Hanseeuw, Bernard J.; Rentz, Dorene M.; Johnson, Keith A.; Sperling, Reisa A.
Abstract : Background and Objectives: Alzheimer disease (AD) clinical trials are moving earlier in the disease process according to emerging signs of β-amyloid (Aβ) and tau pathology. If early treatment is the right time for intervention, it is critical to find the right test to optimize cognitive outcome measures for clinical trials. We sought to identify cognitive measures associated with the earliest detectable signs of emerging Aβ and tau pathology. Methods: One hundred twelve clinically normal adults with longitudinal Pittsburgh compound B (PiB)-PET, 18 F-flortaucipir (FTP)-PET, and cognitive data for ≥7 years were included from the Harvard Aging Brain Study (HABS). Analyses assessed those initially classified as PiB− (less than Centiloid [CL] 20) and then expanded to include PiB+ individuals up to CL40, the approximate threshold beyond which neocortical tau proliferation begins. Separate linear mixed-effects models assessed the effects of emerging global Aβ (PiB slope) and tau (baseline FTP level and FTP slope) in the entorhinal and inferior temporal (IT) cortices on multiple cognitive tasks and the Preclinical Alzheimer's Cognitive Composite (PACC) over time. Results: Steeper PiB slopes were associated with declining processing speed (Digit Symbol Substitution Test [DSST], Trail Making Test Part A) in those <CL20 and expanded to include learning/memory retrieval (FCSRT-FR], Selective Reminding Test Total Recall [SRT-tr], Logical Memory Immediate Recall) in the <CL40 group. FTP had limited effects under CL20, with only rising right IT FTP slope related to declining FCSRT-FR and SRT-tr learning/memory retrieval. When we expanded to include those initially <CL40, rising FTP level or slope was related to declines across all tasks, and PiB slope effects on memory retrieval but not DSST score were reduced. A composite measure of processing speed and memory retrieval tasks provided the strongest prediction of decline under CL40, while PACC score remained optimal at high levels of Aβ (>CL40). Discussion: Early, Aβ-mediated cognitive slowing was detected for processing speed measures, while early memory retrieval declines were associated with emerging Aβ and tau pathology. Composites of these measures may help determine whether anti-Aβ or anti-tau therapies administered at the first signs of pathology might preserve cognitive function. Classification of Evidence: This study provides Class I evidence that in clinically normal older adults, emerging PET-detected AD pathology is associated with declining processing speeds and memory retrieval.